THE APPROXIMATION OF CRIMINAL LAWS IN THE EUROPEAN UNION: THE DEMISE OF INCONGRUENCY OF LEGAL TERMINOLOGY IN LEGAL TRANSLATION? - BEDNAREK, Grażyna (Comparative Legilinguistics, 2012)
In legal translation, one of the major challenges is the translation of legal concepts, which may be attributed to the fact that translation of legal texts entails translation not only from one legal language into another legal language, but primarily from one legal system into another legal system. It is generally acknowledged that the incongruency of the SL and TL legal systems makes it impossible for the elements of one legal system to be automatically transposed into another. For this reason, the translation of legal concepts is characterized by the existence of near, partial, and non-equivalents. There are many words, which although perceived as linguistic equivalents, conceptually and/or referentially constitute only partial or non-equivalents. In what follows, I wish to investigate, whether the approximation of serious, transnational criminal offences in the European Union (EU) leads to the demise of the incongruency of legal terminology. The paper encompasses three major parts, of which the first introduces the existence of the incongruency of legal terminology, the successive part expounds the intricate mechanisms that lead to the approximation of criminal laws, and the final provides a comparative analysis of the approximated legal concepts relating to chosen serious criminal offences revealing its consequences on legal translation.